The Variable Characteristics of Human Papillomavirus in Squamous Cell Carcinoma and Adenocarcinoma of Cervix in China. Issue 4 (October 2018) - Chen, Wen; Sun, Haikui; Molijn, Anco; Zeng, Liang; Kang, Leni; Jenkins, David; Zhang, Shaokai; Cui, Jianfeng; Wu, Zeni; Pirog, Edyta; Shen, Guihua; Zhang, Xun; et al.
Abstract : Objective: A hospital-based multicenter, retrospective study was conducted to compare the distribution of human papillomavirus (HPV) in squamous cell carcinoma (SCC) and cervical adenocarcinoma (CADC) in China. Methods: Paraffin-embedded tissue blocks diagnosed as SCC and CADC across China were collected, as well as the total number of diagnosed invasive cervical cancer of the 9 selected centers. DNA enzyme immunoassay, reverse hybridization, and multiplex type-specific polymerase chain reaction were used for HPV genotyping. Results: The ratios of CADC to SCC were increasing from 2005 to 2010, in parallel with HPV prevalence in CADC. In 630 patients with SCC (mean ± SD age, 45.40 ± 10.30) and 718 patients with CADC (mean ± SD age, 46.09 ± 10.59) recruited, HPV prevalence rates were 97.6% and 74.5%, respectively. Human papillomavirus viral load for SCC is significantly higher than that for CADC. Most common HPV types distributed in SCC and CADC were HPV-16 (78.5%, 75.1%–81.6%; 47.1%, 42.9%–51.3%), HPV-18 (8.0%, 6.1%–10.4%; 41.1%, 37.0%–45.3%), HPV-52 (2.3%, 1.4%–3.8%; 5.6%, 4.0%–7.9%), and HPV-45 (1.1%, 0.6%–2.3%; 3.9%, 2.6%–5.9%). Different diagnostic mean ± SD age for HPV-16/HPV-18 versus other high-risk HPV types were observed: SCC (44.5 ± 9.94 vs 51.0 ± 10.83, p < .05) and CADC (44.1 ± 9.44 vs 47.4 ± 10.41, p = .006). For HPV-negative cases, mean ± SD age was 46.1 ± 10.73 in SCC and 50.3 ± 11.85 in CADC, which were older than the positive (45.4 ± 10.31, 44.5 ± 9.64). HPV-16 and HPV-18 were the most frequent HPV types in both histological types, and HPV-18 was more frequent in CADC than in SCC. Conclusions: Human papillomavirus infection was identified more often in SCC than in CADC. Women with HPV-associated cancers, especially HPV-16/HPV-18, were of a younger age at diagnosis when compared with non–HPV-associated cancers. Abstract : Evidence of HPV and specific HPV genotypes differed in frequency for cervical squamous cell carcinoma compared to adenocarcinoma in China.